2016
DOI: 10.1093/toxsci/kfw186
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Highlight: Screening ToxCast Prioritized Chemicals forPPARGFunction in a Human Adipose-Derived Stem Cell Model of Adipogenesis

Abstract: The developmental origins of obesity hypothesis posits a multifaceted contribution of factors to the fetal origins of obesity and metabolic disease. Adipocyte hyperplasia in gestation and early childhood may result in predisposition for obesity later in life. Rodent in vitro and in vivo studies indicate that some chemicals may directly affect adipose progenitor cell differentiation, but the human relevance of these findings is unclear. The nuclear receptor peroxisome proliferator-activated receptor gamma (PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 52 publications
(65 reference statements)
1
29
0
Order By: Relevance
“…A variety of other potential obesogens have been identified that are known to act on pre‐adipocytes or MSCs to promote adipogenic differentiation . It was recently shown that TBT and other chemicals that activate RXR commit MSCs to the adipose lineage by activating RXR, but not PPARγ.…”
Section: Obesogens Reprogram Stem Cell Fatementioning
confidence: 99%
See 1 more Smart Citation
“…A variety of other potential obesogens have been identified that are known to act on pre‐adipocytes or MSCs to promote adipogenic differentiation . It was recently shown that TBT and other chemicals that activate RXR commit MSCs to the adipose lineage by activating RXR, but not PPARγ.…”
Section: Obesogens Reprogram Stem Cell Fatementioning
confidence: 99%
“…A variety of other potential obesogens have been identified that are known to act on pre-adipocytes or MSCs to promote adipogenic differentiation. 90,91 It was recently shown that TBT and other chemicals that activate RXR commit MSCs to the adipose lineage by activating RXR, but not PPARγ. TBT and pharmacological RXR agonists derepress genes important for adipogenic commitment by decreasing deposition of the repressive chromatin mark, histone 3 lysine 27 trimethyl (H3K27 me3 ) in the promoters and regulatory regions of these genes, leading to increased expression of their mRNAs.…”
Section: Stem Cell Fatementioning
confidence: 99%
“…Adipogenesis is a tightly controlled program of gene expression that drives the differentiation of committed pre-adipocytes to mature functional adipocytes (Fig. 4) This assay was found to be useful for evaluating chemical-induced adipogenesis via activation of PPARγ and GR (Foley et al, 2017), (Hartman et al, 2018). Testing GR agonists and antagonists that are also used for various clinical applications in the human population (Hartman et al, 2018) demonstrated that the assay was able to predict concentrations at which GR activity would be expected for natural and synthetic glucocorticoids.…”
Section: On Revolution: a New Paradigm For Risk Assessment Needs A Nementioning
confidence: 99%
“…The obesogen hypothesis suggests that chemical induction of adipogenesis in prenatal development may predispose individuals to metabolic disease later in life by increasing their adipose stores. A novel human adipose-derived stem cell (hASC) assay to assess the adipogenic effects of enviromental chemicals has been developed(Foley et al, 2017),(Hartman et al, 2018) (Foley et al, 2015) based on the current knowledge of the key biological pathways that drive adipocyte differentiation applying a hormone cocktail of Peroxisome proliferator-activated receptor gamma (PPARγ), Glucocorticoidrezeptor (GR), and CCAAT/enhancerbinding-protein (C/EBP) agonists and insulin. This cocktail drives differentiation of human adipocytederived stem cells to a fully mature phenotype capable of lipid accumulation and adipokine secretion.…”
mentioning
confidence: 99%
“…For adipogenic activity, percent activities (efficacies) across the tested dose response range were calculated relative to the maximal rosiglitazone-induced fold induction over intra-assay differentiated vehicle controls (0.1% DMSO), after correcting for background fluorescence. Rosiglitazone was utilized as the positive control herein due to selective, robust, and potent binding to PPARγ (51)(52)(53); it is often utilized as a positive control in adipogenesis assays (54)(55)(56)(57)(58)(59)(60), and allows for easier comparisons to be made in test chemical response across laboratories and studies. DNA content was calculated as percent change from vehicle controls for each chemical at each concentration and was then used to normalize total triglyceride values to obtain triglyceride content per unit DNA (as a proxy for triglyceride accumulation per cell).…”
Section: T3-l1 Triglyceride Accumulation Cell Proliferation and Cementioning
confidence: 99%